THE EFFECT OF PROBIOCORM PROBIOTIC ON MORPHO-PHYSIOLOGICAL PARAMETERS OF RABBITS’ BLOOD (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Probiotic feeds have a positive effect on the general condition of the organism, reproduction and development of rabbits, hematological and biochemical parameters of animals , morphofunctional state of the liver and excretory organs. Its addition to the ration of animals in the amount of 200 g/t onna helps to adapt easily and better to the conditions of intensive technologies that are currently widely used . The moderate functioning of the body, its growth and development, and resistance to various diseases depend on the nutritional value and proper organization of the feeding. Regular and orderly feeding is the basis for getting good quality meat and fur. If the feeding is organized correctly, the quality indicators of any studied breed will improve. On the other hand, incorrect or poor feeding of rabbits causes even in the best breeds productivity and endurance ability, that is, resistance to diseases to decrease. Pro Bio Korm one of the types of food consumed by animals is a nutritional supplement made by local probiotic bacteria. Universal food additive improves the quality of additional food and digestibility and absorption of substances, prevents and treats various bacterial diseases of animals as well as increases productivity of agricultural animals and improves its quality.